Handbook for the heart : original writings on love - Carlson, Richard; Carlson, Richard, 1961 May 16-; Shield, Benjamin, 1964- (Boston, MA : Little, Brown and Co., 1996)
This program contains original essays created especially for the Handbook for the Heart by some of the most important bestselling writers of today
Keywords: Love; Love -- Religious aspects